Nonlinear Nexus Between ESG Scores and Corporate Performance of Insurance Companies in the MENAT Region: Moderating the Effect of Institutional Quality - Rewayda Tobar (Risks)
Although the relationship between ESG performance and firm performance has been the subject of several studies, the nonlinear relationship between ESG performance and the corporate performance of insurance companies remains less explored, specifically in the Middle East, North Africa, and Turkey (MENAT) region. Moreover, the moderating effect of institutional quality on this relationship has not been examined. To fill this gap, this paper investigates the nonlinear impact of ESG performance on the financial performance of insurance companies in the MENAT region, as well as the moderating effect of institutional quality. To achieve this, a sample of 31 insurance companies located in the seven MENAT countries was constructed over the period 2017–2022. The sample was selected based on the completeness and availability of ESG-related data. This ensured a standardized dataset to enhance the reliability of the results. To estimate this relationship, the System Generalized Method of Moments (SGMM) was used. This technique was used to address endogeneity issues. The empirical results indicate that the performance of the insurance companies is better for those with better ESG performance. Moreover, the quality of institutions is an even more important factor in enhancing the ESG practices–corporate performance nexus. More in-depth analysis is needed to show how these various relationships might be altered with ESG criteria. The findings of this research would, therefore, be beneficial to insurers in terms of an increased understanding of how effective integration of ESG practices, both at the institutional and company level, could be streamlined to enhance their long-term competitiveness and profitability.